2018
DOI: 10.1177/000313481808400838
|View full text |Cite
|
Sign up to set email alerts
|

Defining Outcomes after Colon Resection in Blunt Trauma: Is Diversion or Primary Anastomosis More Favorable?

Abstract: Previous literature demonstrates the safety of primary repair in penetrating colon injury requiring resection, without the creation of a diverting ostomy. It is unknown whether a similar approach can be applied to patients with blunt colon injury. The aim of this study was to measure outcomes in patients who underwent colon resection with and without ostomy creation after blunt trauma injury to help direct future management. Using the National Trauma Data Bank for years 2008 to 2012, we identified patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Demetriades et al 13 in their multicentre prospective study of 297 patients found that severe faecal contamination, transfusion ≥4 units with 24 hours or a single-agent antibiotic prophylaxis to carry significant risk for abdominal complications 13. Recently, Lasinski et al 14 in their multicentre retrospective study of 581 patients treated with either primary anastomosis after resection or with diverting colostomy did not have any difference in mortality, hence advocating for primary repair after resection 14…”
Section: Discussionmentioning
confidence: 99%
“…Demetriades et al 13 in their multicentre prospective study of 297 patients found that severe faecal contamination, transfusion ≥4 units with 24 hours or a single-agent antibiotic prophylaxis to carry significant risk for abdominal complications 13. Recently, Lasinski et al 14 in their multicentre retrospective study of 581 patients treated with either primary anastomosis after resection or with diverting colostomy did not have any difference in mortality, hence advocating for primary repair after resection 14…”
Section: Discussionmentioning
confidence: 99%
“…However, restoration of bowel continuity after a Hartmann's procedure is associated with significant morbidity and resource utilization and many of these patients do not undergo reversal surgery, remaining with a permanent stoma [274,275]. Given the absence of high-quality evidence in the specific population of AFB, we refer to the trauma literature [276][277][278][279] and to the WSES guidelines for the management of acute colonic diverticulitis [280] and for the management of iatrogenic colonoscopy perforation [281]: we suggest that a resection with primary anastomosis, with or without a diverting stoma, may be performed in otherwise healthy patients, with good tissue quality and without risk factors for anastomotic leakage, in case a primary suture is not feasible. On the other hand, Hartmann's procedure is suggested for the management diffuse peritonitis in critically ill patients and in selected patients with multiple comorbidities and risk factors for anastomotic leakage (i.e., requirement of vasoactive drugs, hemodynamic instability, corticosteroid therapy).…”
Section: D -In Patients With Retained Anorectal Foreign Body What Are the Indications For Surgical Treatment And What Is The Appropriate mentioning
confidence: 99%